PENINGKATAN KUALITAS PRODUK SHORTENING MENGGUNAKAN PENDEKATAN DMAIC SIX SIGMA DI PT BEST GRESIK - Dwi Junianto Junianto; Ela Rolita Arifianti; Narto Narto (Universitas Putera Batam, 2021)
PT. BEST is a manufacturing industry that is engaged in processing palm cooking oil, one of the processed products from the production process is shortening which is margarine for processed household products. In the production process found a very high level of product defects, several factors that become obstacles that cause product defects. The high level of product defects resulted in low product quality and a decrease in the amount of production. Product quality improvement using the DMAIC Six Sigma concept approach is able to identify the factors causing product defects and improve product quality. The purpose of this study is to identify the factors that cause product defects and provide suggestions for improvements to improve the quality of Shortening products. The results of the analysis show that the DPMO value is 22,090.93 with a sigma level of 3.5124 with the largest defect rate being cardboard defects of 40.83%. Proposed improvements provide training to operators to improve machine operating skills, periodic inspection of raw materials to maintain the quality of raw materials, periodic machine repairs to avoid a decrease in the quality of production.